THE RELATIONSHIP OF INDEPENDENT CURRICULUM LEARNING WITH TEACHERS' MENTAL HEALTH - Mulyaningsih, Trisistu; Inayah, Zufra (Journal of Public Health Science Research (JPHSR), 2023)
Enhancement prevalence mental disorders of the population age above 15 by 3.7% of 2013-2018 so _ around 12 million Indonesian people experience depression , mental health related elementary teachers usability _ technology and perceptions of the effectiveness of online learning in the COVID-19 era also contributed in enhancement prevalence the . Objective study For analyze learning curriculum independent with teacher mental health . Study done in a manner quantitative and is analytic observational with des ai n cross sectional . Population is teacher at YPI Darussalam 2 Cerme Gresik Vocational School with total sampling technique as many as 32 people . Instrument research , questionnaire The Mental Health Inventory-38 (MHI-38) . Analysis use test Kendall's tau-b on level trust 95%. Results analysis learning curriculum independent almost entirely fulfilled by 84.4% and teacher mental health almost all good by 78.1% with P value = 0.003 < α = 0.05. It means There is connection between learning curriculum independent with teacher mental health